FREEDOM IN PRE-ISLAMIC POETRY - Abdulrahman Jaber Shakir (Scholar Express Journals, 2023)
The pre-Islamic society was built on a tribal basis, where two main classes emerged in that society, the clear class and the slave class, and the life of humiliation that the slaves lived, and the harsh treatment they suffered, incited them to revolt, and that this class disparity based on color and race led to igniting The fire of hatred between the people of one tribe, and a bloody conflict erupted between them, and the relationship of man with his society at the time had several forms: either full involvement with the tribe and speaking in its language, or rebellion and rebellion against society, and the establishment of a new society based on equality and social justice, and the best example of this is the group of tramps. This suffering affected the hearts of the poets among them, and was reflected in their poetry, so their poems knew the tendency to brag about their courage, and to portray their suffering from poverty and destitution, with an emphasis on their self-esteem and their preference for suffering and hunger as a price for their freedom, over satiety in exchange for their slavery and submission .
Keywords: freedom; poetry; freedom in poetry; pre-Islamic poetry